Gender, culture and exclusion of women in educational leadership - Muzvidziwa, Irene (CSSALL Publishers, 2016)
Generally women are the majority in the teaching field especially in primary schools, yet they constitute the least number in positions of authority within the education system. This article examines, the underlying reasons for this under representation of women through a gendered analytical framework, focusing on an empirical research of women deputy heads that was conducted in one of the provinces in Zimbabwe using qualitative interviews. Despite efforts to increase the representation of women in school leadership positions, their numbers have remained very low. Research that I have conducted in the last ten years do show that gender roles, culture and gender relations influence women’s rise into leadership positions. Arising from these observations are questions such as: why do women’s numbers in managerial and leadership positions continue to be low? What messages do women aspiring for leadership positions get from their female counterparts who act as their role models? The issues that emerged from the study and literature included lack of acceptance of women leaders by both male and female teaching staff, the assumption that leadership is for men was supposedly linked to women’s lack of aspiration. The possible barriers to women’s advancement and the strategies that create opportunities for more women in educational leadership was linked to cultural constraints from both the society and organisational institutions thus including the challenges women face as educational leaders.